LIDAR Sensing Technology Using in Transport Systems for Tram Motion Control - Patlins, A.; Kunicina, N.; Zhiravecka, A.; Shukaeva, S. (Elektronika ir Elektrotechnika, 2010)
The system of passenger transport is an integral part of each city. Well developed infrastructure and the reliable control system of a municipal transportation create favourable preconditions for municipal economy development as a whole. In this research motion control systems LIDAR sensors are examined. The work subject is quite modern because nowadays such an analysis of sensors appliance can decrease effect of human factor to traffic control. The main idea of this research is to install distance measuring sensor to trams. The LIDAR systems can be used for such purpose. The control algorithm developed in scope of this work calculates tram braking path taking as input the LIDAR provided signal.